PABRA Narrative Annual Report: January - December 2010 - Pan-Africa Bean Research Alliance (Pan-Africa Bean Research Alliance, 2010)
The goal of the Pan-Africa Bean Research Alliance (PABRA) is to improve the productivity and the nutritional quality of beans so as to improve the income, nutrition and food security of the rural and urban poor particularly women. Through its research and development program, supported by a consortium of donors and (CIDA and SDC, BMGF, H+, Kirkhouse Trsut, SRO etc) PABRA takes advantage of the complementarities and synergy derived from its partnership. The latter include NARIs, NGOs, GOs, extension services providers and private sector. This report covers the period January – December 2010 and is structured on the basis of a revised RBM framework. It also offers a cumulative progress towards achieving immediate, intermediate and ultimate outcomes against set targets. But it also reports on output results.